Impact of tumour morphology on renal function decline after partial nephrectomy. (28th May 2013) - Mehrazin, Reza; Palazzi, Kerrin L.; Kopp, Ryan P.; Colangelo, Caroline J.; Stroup, Sean P.; Masterson, James H.; Liss, Michael A.; Cohen, Seth A.; Jabaji, Ramzi; Park, Samuel K.; Patterson, Anthony L.; L'Esperance, James O.; et al.
<x xml:space="preserve">Abstract</x> Objective To examine the association of renal morphology with renal function after partial nephrectomy (PN). Patients and Methods We conducted a multi‐institutional retrospective analysis of 322 PNs performed between 2003 and 2011. The RENAL nephrometry score for each lesion was determined and the estimated glomerular filtration rate (eGFR) was calculated preoperatively and at last follow‐up. We divided patients into two RENAL nephrometry score groups, low (<8) and high (≥8), and analysed and compared the outcomes of each group. The primary outcome was median change in eGFR between preoperative and last follow‐up (ΔeGFR). The secondary outcome was eGFR <60 mL/min/1.73m2 at last follow‐up. Multivariable analysis was conducted to evaluate the risk factors for eGFR <60 mL/min/1.73 m2 at last follow‐up. Results The median (interquartile range) follow‐up was 25.2 (13.5–39.3) months. Low (n = 165) and high (n = 157) RENAL score groups were well‐matched for baseline eGFR. The median tumour size (4.2 vs 2.4 cm, P < 0.001) was greater for the high group. In all, 64% of the low and 88.2% of the high RENAL score group (P < 0.001) had decreased eGFR at last follow‐up. Median eGFR was −7 for the low vs −13.8 mL/min/1.73 m2 for the high group (P = 0.001); eGFR <60 mL/min/1.73 m2 at last follow‐up was 27.3% for the low vs 37.6% for the high group (P = 0.057). Linear regression analysis showed that for each 1‐point increase in RENAL score, there was 2.5% decrease in eGFR (P = 0.002); for each 1‐cm increase in tumour size, there was 1.8% decrease in eGFR (P = 0.013). Area under curve analyses showed no significant difference between RENAL score and tumour size for prediction of de novo eGFR <60 mL/min/1.73 m2 (P = 0.920) and ΔeGFR ≥50% (P = 0.85). Multivariable analysis showed that increasing RENAL score (odds ratio [OR] 1.24, P = 0.046) and decreasing preoperative eGFR (OR 1.10, P < 0.001) were risk factors for eGFR <60 mL/min/1.73 m2 at last follow‐up. Conclusions Increasing RENAL nephrometry score is an independent risk factor for eGFR <60 mL/min/1.73 m2 after PN. RENAL nephrometry score may serve as an additional measure for risk stratification before PN, but further investigation is required.